2006
DOI: 10.1017/s0140525x06369105
|View full text |Cite
|
Sign up to set email alerts
|

Learning that there is life after death

Abstract: The present article examines how people's belief in an afterlife, as well as closely related supernatural beliefs, may open an empirical backdoor to our understanding of the evolution of human social cognition. Recent findings and logic from the cognitive sciences contribute to a novel theory of existential psychology, one that is grounded in the tenets of Darwinian natural selection. Many of the predominant questions of existential psychology strike at the heart of cognitive science. They involve: causal attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
7
0
1
Order By: Relevance
“…An increase in continuity judgments by a religious context would be consistent with the theory that afterlife beliefs are acquired through exposure to religious ideas and practices (Bloom, 2007;Harris & Astuti, 2006). An alternative possibility is that responses in one context reflected a default mode of reasoning, while the other context biased responses toward increased continuity or discontinuity reasoning.…”
Section: Context Effectssupporting
confidence: 71%
“…An increase in continuity judgments by a religious context would be consistent with the theory that afterlife beliefs are acquired through exposure to religious ideas and practices (Bloom, 2007;Harris & Astuti, 2006). An alternative possibility is that responses in one context reflected a default mode of reasoning, while the other context biased responses toward increased continuity or discontinuity reasoning.…”
Section: Context Effectssupporting
confidence: 71%
“…Thus, children held two distinct ways of conceptualizing death, a biological conception and a metaphysical conception. Such findings demonstrate children's ability to reason from different perspectives depending on the story context; as a result, some researchers have suggested that when adults tell children stories about what happens after death, children's understanding of death is sometimes affected (Harris & Astuti, 2006). What is not yet documented in the literature is the way in which children may be learning and creating their personal meanings of death, definitions that may encompass both biological and spiritual or religious ideas.…”
Section: Children's Understanding Of Deathmentioning
confidence: 98%
“…he controversy in the literature about the origin of afterlife beliefs -cognitive predisposition (Bering, 2002(Bering, , 2006Bering and Bjorklund, 2004;Bering et al, 2005) or cultural learning (Harris and Astuti, 2006;Astuti and Harris, 2008) -has been sustained by contradictory findings in developmental as well as cultural data and accentuates the need for more cross-cultural and developmental studies in this area.…”
Section: Future Directionsmentioning
confidence: 99%